2015
DOI: 10.1097/grf.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar and Vaginal Atrophy

Abstract: Vulvovaginal atrophy is a common condition associated with decreased estrogenization of the vaginal tissue. Symptoms include vaginal dryness, irritation, itching, soreness, burning, dyspareunia, discharge, urinary frequency, and urgency. It can occur at any time in a woman's life cycle, although more commonly in the postmenopausal phase, during which the prevalence is approximately 50%. Despite the high prevalence and the substantial effect on quality of life, vulvovaginal atrophy often remains underreported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 21 publications
0
21
0
3
Order By: Relevance
“…VVA is a widespread condition, with symptoms affecting around half of all peri- and postmenopausal women 16 . These symptoms can have a substantial negative impact on interpersonal relationships, quality of life, daily activities, and sexual function 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VVA is a widespread condition, with symptoms affecting around half of all peri- and postmenopausal women 16 . These symptoms can have a substantial negative impact on interpersonal relationships, quality of life, daily activities, and sexual function 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that a lack of awareness among women about the physiological changes associated with the menopause and the availability of effective and well-tolerated treatments, reluctance to discuss symptoms with HCPs, safety concerns, inconvenience, and inadequate symptom relief from available treatments are potential barriers to seeking and using treatment 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…1 A component of genitourinary syndrome of menopause, 2 VVA is a chronic, progressive condition that clinically manifests as vaginal dryness, irritation, dysuria, and pain (dyspareunia) or bleeding with sexual activity. 3 VVA, unlike vasomotor symptoms, is progressive and not likely to resolve without treatment. 4 …”
Section: Introductionmentioning
confidence: 99%
“…VVA is a component of the genitourinary syndrome of menopause (GSM), and collectively includes changes to the labia majora/minora, clitoris, vestibule/introitus, vagina, urethra, and bladder. 1 , 2 A review of surveys reported up to two-thirds of women have physical evidence of VVA, 3 and approximately 50% of postmenopausal women have VVA symptoms. 4 These symptoms may include vaginal dryness, irritation, itching, dysuria, and/or pain or bleeding with sexual activity.…”
mentioning
confidence: 99%